Envisioning Africa : racism and imperialism in Conrad's Heart of darkness - Firchow, Peter Edgerly, 1937- (University Press of Kentucky, 2000)
For one hundred years, Heart of Darkness has been among the most widely read and taught novels in the English language. Hailed as an incisive indictment of European imperialism in Africa upon its publication in 1899, more recently it has been repeatedly denounced as racist and imperialist. Peter Firchow counters these claims, and his carefully argued response allows the charges of Conrad's alleged bias to be evaluated as objectively as possible. He begins by contrasting the meanings of race, racism, and imperialism in Conrad's day to those of our own time. Firchow then argues that Heart of D.